Coaching behaviors and stakeholders' views of coaches' efficacy - Teatro, C.; Kulinna, P. H.; van der Mars, H.; Thompson, M.; JaYoun, K. (International Journal of Sports Science & Coaching, 2017)
There appears to be a relationship between coaching efficacy and athlete satisfaction, confidence, and performance, as well as coach behavior. However, little research exists, specifically within a high school setting, examining the relationship between coaches' perceptions of efficacy and those of stakeholders (parents and athletes). The purpose of this research was to examine the relationship between coaches' efficacy and stakeholders' views of coach efficacy. A sample of 516 coaches, 115 athletes, and 103 parents were recruited. Coaches have significantly higher levels of coaching efficacy on all four efficacy domains than the ratings from athletes and parents, while no differences between athlete and parent scores exist. Although coaches reported relatively high levels of coaching efficacy, they reported the lowest efficacy for motivation. Athletes concurred, providing the lowest scores for coaches in motivation. Implications for coaching education are discussed, including a greater need for training on implementing athlete motivation techniques. ABSTRACT FROM AUTHOR